Comparing the immigrant-native pay gap: A novel evidence from home and host countries - Andrej Cupák; Pavel Ciaian; D'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2021)
We estimate wage differentials and compare inequality trends between foreign-born and native-born workers across developed economies and developing economies. We leverage large internationally harmonised microdata covering 21 countries, 20 years and 1.5 million individuals and employ Blinder-Oaxaca counterfactual decomposition techniques. We find that vis-à-vis comparable workers born in developed countries, the workers born in developing economies are disadvantaged both in their home country labour markets and - if migrating - also in developed host countries. The estimated Blinder-Oaxaca wage differentials suggest the opposite for workers born in developed countries - their wages are higher not only in developed countries but for migrants also in developing host countries. After accounting for personal and job-related characteristics, at least 28% of the total native-to-migrant wage gap still remains unexplained. The unexplained wage gap has increased during the last decade and can be attributed to the labour market discrimination, differences in unobserved job characteristics, variation in unobserved skills, and the institutional labour market framework.
Keywords: D31; J15; J7; 330; labour market; wage gaps; immigrants; decomposition